(untitled) (Huellas, 2019)
A Spatial Data Infrastructure (SDI) is a set of tools that, by complying with the guidelines issued by the different governments that implement it, should allow both official institutions and organizations, as well as society in general, to have access to official geo-referenced information, under conditions which are institutionally determined for each type of user. These tools intend to be operative and meet national and international standards that facilitate access, in an interoperable way, to the geographic information (GI) generated by the different official institutions. After having worked more than thirteen years to launch the SDI in Argentina, many inequalities are observed among the different jurisdictions adhering to the project. It is difficult to create a national SDI if the institutions do not previously develop their own SDIs. Establishing the national SDI implies a change of paradigm in the management and use of the GI, which allows democratization to be achieved in the use of this type of information.